2012
DOI: 10.1111/j.1755-3768.2011.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

The 7‐year cumulative incidence of cornea guttata and morphological changes in the corneal endothelium in the Reykjavik Eye Study

Abstract: ABSTRACT.Purpose: To examine the corneal endothelium and establish the 7-year cumulative incidence of cornea guttata (CG). Methods: Population-based prospective cohort study with 573 participants (third wave of the Reykjavik Eye Study (RES) in 2008). Four hundred and thirty-seven subjects had either right or left eyes available for analysis after excluding confounding eye conditions. The baseline for eyes at risk for developing CG is the second wave of the RES in 2001. Participants underwent specular microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…Despite the absence of preoperative specular microscopy images of these patients, based on the prevalence of guttae in the normal population,2 5 we assume that this finding was simply not detected before surgery.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Despite the absence of preoperative specular microscopy images of these patients, based on the prevalence of guttae in the normal population,2 5 we assume that this finding was simply not detected before surgery.…”
Section: Discussionmentioning
confidence: 85%
“…The prevalence of central corneal guttae in patients older than 40 or 50 years varied in several studies from 3.8% to 70% 2 5. In particular, Borderie and co-workers found isolated guttae and grouped guttae in 25.6% and 4.8%, respectively, of 168 donor corneas for PK 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special attention was given to the corneal examination and patients with guttata, corneal oedema or other pathological corneal findings as well as those with a known history of Fuchs endothelial dystrophy were excluded from the study. Zoega et al reported that mean corneal endothelial cell density in patients with no guttata present was 2495 ± 29 (cells per mm 2 ), suggesting that patients with no evidence of guttata on clinical examination have normal corneal endothelial cell counts. Considering the meticulous preoperative examination and the data from the above quoted study, we feel that preoperative ECD would not have altered our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…F uchs' endothelial dystrophy (FECD) is a corneal disease accompanied by abnormality of the Descemet membrane indicated by polymegethism (irregularly shaped cells) and polymorphism (variable shape of cells) in addition to a considerable loss of the multifunctional, nondegenerative, corneal endothelial cells. [1][2][3] The progressive decrease of cell density is accompanied by an increase in the deposition of the extracellular matrix and thickening of Descemet membrane that accumulates in the form of granular guttae leading to corneal edema and decreased visual acuity. 3,4 FECD is associated with genetic mutations, [4][5][6][7] as well as environmental influences, 7 age and sex 8 among other possible factors.…”
mentioning
confidence: 99%